The Coffee Market Integration in Lampung Province - Irmayani Noer; Fitriani Fitriani; Agus Agus (Jurnal Ilmiah ESAI, 2012)
The research conduct at two production centre in Lampung Province, Tanggamus and West of Lampung Regency.  While marketing centre was Bandar Lampung City.  The research focus on the coffee marketing system from two production centre to Bandar Lampung City. The aims of rersearch was analysis coffee marketing system with marketing integration approach.  Respondent sample came from several sources such as farmer producer, trader in rural area, district, and also at regency level with purposive and proportional sampling method.  The model of coffee marketing system did by structure or marketing integration. The research performed that the price of coffee at the third level marketing in Lampung Province has strong and positive correlation.   The rate of price change at producer level   was smaller than the price at exporter and global market. It indicates that the monopsony or oligopsony power still worked.   In the long term, the coffee market will integrate between producer level and the exporter or global market.  Keywords:  Coffee, marketing, integration, producer, level